Luteal phase support post IVF: individualized early stop. Issue 5 (November 2015) - Segal, Linoy; Breyzman, Tatiana; Kol, Shahar
Abstract: While the need for progesterone-based luteal phase support is well documented, the required treatment duration is not well established, and a practitioners' survey showed a wide range of empiric stopping points. It is suggested that an early stop can be based on assessing endogenous luteal activity on the day of pregnancy test. To examine this approach, data were retrospectively collected on 99 patients with positive pregnancy test and high serum concentrations of oestradiol and progesterone (≥1000 pmol/l and ≥110 nmol/l, respectively), whose luteal support was stopped, and compared with those of 85 patients who did not meet the above criteria, and so luteal support was continued until gestational week 9. Both groups were comparable in terms of live birth and miscarriage rates. We conclude that in the face of strong endogenous luteal activity, exogenous support can be stopped on pregnancy test day, without affecting pregnancy outcome. Further research is needed to substantiate this finding.